2018
DOI: 10.1080/21541264.2018.1539615
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of transcriptional cyclin-dependent kinases

Abstract: The fact that many cancer types display transcriptional addiction driven by dysregulation of oncogenic enhancers and transcription factors has led to increased interest in a group of protein kinases, known as transcriptional cyclin dependent kinases (tCDKs), as potential therapeutic targets. Despite early reservations about targeting a process that is essential to healthy cell types, there is now evidence that targeting tCDKs could provide enough therapeutic window to be effective in the clinic. Here, we discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 147 publications
(215 reference statements)
1
92
0
1
Order By: Relevance
“…When the initiating transcription occurs, the Ser5 phosphorylation level decreases, while Ser2 and Tyr1 phosphorylation increases to promote transcriptional elongation. During transcription termination, Tyr1 is dephosphorylated firstly, closely followed by Ser5, Ser7, and Ser2, which permits restarting the transcription cycle [39].…”
Section: The Roles Of Cdks In Transcriptionmentioning
confidence: 99%
“…When the initiating transcription occurs, the Ser5 phosphorylation level decreases, while Ser2 and Tyr1 phosphorylation increases to promote transcriptional elongation. During transcription termination, Tyr1 is dephosphorylated firstly, closely followed by Ser5, Ser7, and Ser2, which permits restarting the transcription cycle [39].…”
Section: The Roles Of Cdks In Transcriptionmentioning
confidence: 99%
“…In general, most cancer cells exhibit defects in cell cycle regulation and gene transcription, which promotes uncontrolled cell proliferation leading to tumorigenesis [9]. Cyclin-dependent kinases (CDKs) are members of the serine/threonine protein kinase family and are involved in cell cycle control and transcription regulation, which play central roles in tumorigenesis [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In tumorigenesis, CDK7 encourages tumor growth by directly linking transcription regulation to cell cycle control. Based on these molecular traits, CDK7 has emerged as an attractive target for novel anti-neoplastic treatments in various cancers, including EOC [8,9]. THZ1, a covalent CDK7 inhibitor, was first described as an antineoplastic agent in T-cell acute lymphoblastic leukemia [13].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its activity in transcription and cell cycle regulation, the human CAK plays an important role in regulating cell growth and division. Consequently, inhibition of the CAK has been found to be a promising strategy for treatment of proliferative diseases (Galbraith et al, 2019;Kwiatkowski et al, 2014). To obtain insight into the covalent binding of the cysteine-reactive anti-cancer compound THZ1 (Kwiatkowski et al, 2014) to CDK7 within the CAK, we have determined the 3.4-Å-resolution structure of THZ1 bound to a CDK7-cyclin H-MAT1D219 complex (CAK-MAT1D219), in which the N-terminal region of MAT1, including its RING domain, has been removed ( Fig.…”
Section: Structural Mechanism Of Irreversible Inhibition Of Cdk7 By Thz1mentioning
confidence: 99%
“…This process is not only important for normal transcription, but also contributes to aberrantly elevated transcription levels in cancer cells. Consequently, transcription-related CDKs have been identified as promising drug targets (Galbraith et al, 2019), and inhibition of CDK7 by compounds such as THZ1 or SY-1365 has been shown to selectively kill cancer cells that require elevated levels of transcription (Hu et al, 2019;Kwiatkowski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%